A retrospective analysis: comparison of nephrotoxicity caused by concurrent weekly cisplatin in patients of head & neck cancer and cervical cancer - Ranjan, Prabhat; Raveendran, A.; Ravichandran, A.; Manickavasagam, M.; Siri, Kavuru Naga; Mondal, Victor; Chakravarthy, Kavi; Lakshmi, Ramya; Vuppumala, Bhargav (International Journal of Research in Medical Sciences, 2025)
Background: Cisplatin is the most common chemotherapeutic drug which is used concurrently with radiation therapy due to its radio sensitizing effect. Cisplatin is known to cause substantial amount of nephrotoxicity and adequate hydration is absolutely essential while administering cisplatin. Once weekly regimen is widely used both in the treatment of head & neck cancers as well as cervical cancer. The main aim of this study is to compare the incidence and severity of nephrotoxicity in patients of head and neck and cervical cancer treated with concurrent chemoradiation Methods: From January 2023 to December 2023, data of 50 patients each of head and neck cancer and cervical cancer patients treated at our institute was evaluated. Cisplatin was used weekly at the dose of 40 mg/m2 with adequate hydration and necessary pre medications in all the patients. CBC, RFT and Serum Electrolytes were done prior to each cycle. RIFLE criteria were used to classify renal impairment Results: 50 patients each of head and neck and cervical cancer were selected. Total 5 cycles of concurrent cisplatin were planned in both the arms according to the institutional protocol. During the course of treatment, Renal impairment was seen in 32 out of 50 patients (64%) in head and neck cancer arm whereas in ca cervix arm it was seen in only 14/50 patients (28%) Conclusions: Renal impairment is more pronounced in head and neck cancer patients as compared to cervical cancer patients thus more aggressive hydration measures are required in patients of head and neck cancer.